Persistent declines in sightings of manta and devil rays (Mobulidae) at a global hotspot in southern Mozambique - Stephanie K. Venables; Christoph A. Rohner; Anna L. Flam; Simon J. Pierce; Andrea D. Marshall (Environmental Biology of Fishes, 2025)
Mobulid rays are among the most vulnerable of chondrichthyans to overexploitation by fisheries due to their low population growth rates. In locations where catch data are lacking, long-term sightings data can provide valuable insight to infer population trends and status. We recorded underwater sighting data of reef manta rays ( Mobula alfredi ), oceanic manta rays ( M. birostris ), and shorthorned pygmy devil rays ( M. kuhlii ) between 2003 and 2023 in the waters off Praia do Tofo in the Inhambane Province, southern Mozambique, one of the major global hotspots for these rays. We modelled sightings data using a hierarchical generalised linear mixed model framework to account for a suite of environmental variables when examining temporal trends. Raw trend models including only ‘year’ as a predictor showed a 99% decline in sightings of reef manta rays, a 92.5% decline in oceanic manta ray sightings, and an 81.3% decline in devil ray sightings over the 20-year study period. The declining trends persisted for reef and oceanic manta rays once a suite of temporal and environmental variables were accounted for, indicating that the declines were driven by external factors not tested in the models. For shorthorned pygmy devil rays, models that incorporated environmental variables did not retain year as a significant predictor and showed a reduced overall decline in sightings of 36.5%. This indicates that the tested predictors were responsible for approximately half of the observed decline. Anthropogenic factors, particularly fisheries mortality, are likely to have played a significant role in the declining sightings of these three Threatened species. Improved conservation and management measures at a national and international level are critical to prevent further declines, which may otherwise lead to localised extinction.